Boosting purely organic room-temperature phosphorescence performance through a host–guest strategy. Issue 40 (29th September 2021) - Li, Mengke; Cai, Xinyi; Chen, Zijian; Liu, Kunkun; Qiu, Weidong; Xie, Wentao; Wang, Liangying; Su, Shi-Jian
Abstract : Several host–guest cocrystal systems with bright and persistent room-temperature phosphorescence were developed by utilizing a phosphorus-containing material as a robust host and newly developed isomeric organic phosphors as guests. Abstract : The host–guest doping system has aroused great attention due to its promising advantage in stimulating bright and persistent room-temperature phosphorescence (RTP). Currently, exploration of the explicit structure–property relationship of bicomponent systems has encountered obstacles. In this work, two sets of heterocyclic isomers showing promising RTP emissions in the solid state were designed and synthesized. By encapsulating these phosphors into a robust phosphorus-containing host, several host–guest cocrystalline systems were further developed, achieving highly efficient RTP performance with a phosphorescence quantum efficiency ( ϕ P ) of ∼26% and lifetime ( τ P ) of ∼32 ms. Detailed photophysical characterization and molecular dynamics (MD) simulation were conducted to reveal the structure–property relationships in such bicomponent systems. It was verified that other than restricting the molecular configuration, the host matrix could also dilute the guest to avoid concentration quenching and provide an external heavy atom effect for the population of triplet excitons, thus boosting the RTP performance of the guest.